Twenty-four-month outcomes of inflammatory choroidal neovascularisation treated with intravitreal anti-vascular endothelial growth factors: a comparison between two treatment regimens. Issue 8 (19th November 2019) - Invernizzi, Alessandro; Pichi, Francesco; Symes, Richard; Zagora, Sophia; Agarwal, Aniruddha Kishandutt; Nguyen, Phuc; Erba, Stefano; Xhepa, Alba; De Simone, Luca; Cimino, Luca; Gillies, Mark C; McCluskey, Peter J
Abstract : Background and aim: There is still no established treatment regimen for eyes with inflammatory choroidal neovascularisation (iCNV) treated with intravitreal anti-vascular endothelial growth factor (VEGF) injections. This study compared the 24-month outcomes of two treatment regimens of anti-VEGF injections in eyes with iCNV. Methods: Eyes with iCNV treated with anti-VEGF injections were divided into two groups: eyes treated with a loading phase of 3 monthly injections and then re-treated as needed (LOADING group) and eyes treated as needed from the beginning (PRN group). Visual acuity (VA), number of injections and iCNV recurrences at 24 months were compared between the groups. Results: Eighty-two eyes were included, 42 in the LOADING and 40 in the PRN group. Baseline VA (mean(SD)) was 57.3 (15.8) letters in the LOADING vs 60.7 (15.6) letters in the PRN group (p=0.32). The VA (mean (95% CI)) increased at 3 months (+14.8 (10.6 to 18.9) and +11.2 (6.4 to 16) letters in the LOADING and PRN group, respectively) and remained significantly higher than baseline over the entire follow-up in both groups (all p<0.001). At 24 months, there was no difference in VA between the LOADING and PRN group (72.3 (14.0) vs 74.7 (11.3) letters, p=0.36) but the LOADING group received significantly more injections (median (Q1–Q3)) than the PRN (4.5 (3–7) vs 2.5 (2–3.2), p<0.0001). The iCNV recurrences were similar in both groups. Conclusions: iCNV responded well to anti-VEGF with significant and sustained VA improvement. The loading phase did not confer any advantage in terms of outcomes. PRN regimen from the beginning was as effective as more intensive treatment.